2020
DOI: 10.1007/s13205-020-02291-5
|View full text |Cite
|
Sign up to set email alerts
|

ddRAD-seq derived genome-wide SNPs, high density linkage map and QTLs for fruit quality traits in strawberry (Fragaria x ananassa)

Abstract: Understanding the genetic determinants are essential for improving the fruit quality traits of strawberry. In this study, we focused on mapping the loci for fruit-length (FL),-diameter (FD),-weight (FW) and-soluble solid content (SSC) using the genome-wide single nucleotide polymorphisms (SNPs) identified via ddRAD-sequencing of the F 1 population raised from Maehyang (♀) X Festival (♂). A total of 12,698 high quality SNPs were identified of which 1554 SNPs that showed significant Mendelian segregation (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 74 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…Likewise, our AX-184477629 marker linked to TSS on 3B is in the same chromosome region as the SSC1 QTL controlling soluble solids content 30 we found in GWAS/QTL published data only a few additional fruit quality QTL located on the same chromosomes as those detected here. Among them are the FW QTL on 5B and the TSS QTL on 5A previously reported 38 on the same chromosomes but in different regions. Thus, thanks to the originality of European accessions included in our study, the genetic diversity of the panel allowed us to reveal new QTL and associated SNP markers, even for well-studied fruit quality traits such as FW and TSS.…”
Section: Novel Markers For the Selection Of Fruit Quality Traitsmentioning
confidence: 99%
“…Likewise, our AX-184477629 marker linked to TSS on 3B is in the same chromosome region as the SSC1 QTL controlling soluble solids content 30 we found in GWAS/QTL published data only a few additional fruit quality QTL located on the same chromosomes as those detected here. Among them are the FW QTL on 5B and the TSS QTL on 5A previously reported 38 on the same chromosomes but in different regions. Thus, thanks to the originality of European accessions included in our study, the genetic diversity of the panel allowed us to reveal new QTL and associated SNP markers, even for well-studied fruit quality traits such as FW and TSS.…”
Section: Novel Markers For the Selection Of Fruit Quality Traitsmentioning
confidence: 99%
“…Genome-wide association study and QTL mapping QTL mapping has been applied frequently for many fruit quality traits including SSC, thanks to handheld refractometers that provide rapid measurements. Biparental (Castro & Lewers, 2016;Lerceteau-Köhler et al, 2012;Natarajan et al, 2020;Rey-Serra et al, 2021;Vallarino et al, 2019;Zorrilla-Fontanesi et al, 2011) and pedigree connected populations (Verma et al, 2017) have been investigated for SSC QTLs using different marker technologies identifying many SSC QTL, yet with few consensus QTL across multiple populations/environments. Moreover, a GWAS analysis with a small sample collection found no significant markers correlating with SSC (Cockerton et al, 2021).…”
Section: 1mentioning
confidence: 99%
“…The genetic control of SSC appears to be complex. Though quantitative trait locus (QTL) have been detected in different studies (Castro & Lewers, 2016; Lerceteau‑Köhler et al., 2012; Natarajan et al., 2020; Vallarino et al., 2019; Verma et al., 2017), few have been stable across environments and breeding programs. Nevertheless, multiple studies have shown moderate heritability and the ability to make gains from selection (Gezan et al., 2017).…”
Section: Flavor‐affecting Metabolites and Their Genetic Controlmentioning
confidence: 99%
“…CAPS/HRM markers have been reported for 'PMR 5' resistance to powdery mildew race 5 in melon [21]. GBS and ddRAD-seq techniques have been used for mapping genes and development of markers in several plant species such as rapeseed, soybean, maize, strawberry and melon [22][23][24][25]. Among these assays, HRM and Kompetitive allele specific PCR (KASP) assays have relatively simple, fast, and cost-effective approaches.…”
Section: Introductionmentioning
confidence: 99%